Capillary electrophoresis as a production tool for asymmetric microhybrids. Issue 14 (17th July 2013) - Fattah, Zahra; Garrigue, Patrick; Goudeau, Bertrand; Lapeyre, Véronique; Kuhn, Alexander; Bouffier, Laurent; Escarpa, Alberto; Pumera, Martin
<x xml:space="preserve">Abstract</x> The site selective electrodeposition of silver metal onto a conducting object such as carbon microtubes (CMTs) in an electrolytic solution could be achieved by means of bipolar electrochemistry. Two half reactions are simultaneously carried out at both extremities of the CMT, which act as a bipolar electrode. The thermodynamic threshold value of the process, which consists in metal electroreduction and concomitant water oxidation is directly related to the length of CMT. That is the reason why, when scaling down the methodology to microscale objects, electric fields in the range of tenths of kilovolts per meter are necessary. In that context, a CE apparatus provides a convenient experimental platform to achieve in a straightforward manner such experimental conditions. We exemplify this methodology with the efficient and quick electroreduction of Ag+ on CMTs from a low‐concentration aqueous electrolytic solution during the migration across a fused capillary. CE allows applying safely a large enough electric field (typically ∼30 kV/m) for the successful modification of 15 to 20 μm‐long substrates. The corresponding hybrid materials have been characterized by optical microscopy as well as SEM and energy‐dispersive X‐ray spectroscopy.